The Implementation of Reward Strategy to Foster EFL Students’ Motivation in Narrative Writing - Aminah, Andi Siti; Salija, Kisman; Atmowardoyo, Haryanto (Har Press Indonesia, 2023)
The object of this research to find out the implementation of reward strategy toward students’ motivation in narrative writing. The researcher used quantitative method and quasi-experimental design as the research methodology. The purpose of this study to investigate the effect of reward strategy toward students’ achievement and to know how the reward strategy can motivate the students in narrative writing. The population in this research was the students class X Mipa SMA N 10 Makassar that consist of 8 classes. Class X Mipa 1 as an experimental group and class X Mipa 3 as control group that consist of 36 students. The data of the research obtained by the result test of pre-test and post-test. The data is analyzed by the writing test and questionnaire. The students’ motivation in narrative writing focus on experimental group. The questionnaire consists of 20 statements. It had been showed with 85 % positive respond. Based on findings above. It can be concluded that the implementation of reward strategy has significant of students writing achievement and motivation.